Differential metabolism of clinically-relevant progestogens in cell lines and tissue: Implications for biological mechanisms. Issue 189 (May 2019) - Skosana, Salndave B.; Woodland, John G.; Cartwright, Meghan; Enfield, Kim; Komane, Maleshigo; Louw-du Toit, Renate; van der Spuy, Zephne; Avenant, Chanel; Africander, Donita; Storbeck, Karl-Heinz; Hapgood, Janet P.
Highlights: Progestins are differentially metabolised in a cell line-specific manner. Progesterone is rapidly metabolised by 24 h in all cell lines investigated. MPA and NET are significantly metabolised in human cervical tissue ex vivo . Metabolism may under-estimate effects determined for progesterone in vitro . Differential metabolism may affect cell-specific therapeutic and side-effects. Abstract: Steroid hormones regulate a variety of physiological processes, including reproductive function, and are widely used in hormonal therapy. Synthetic progestogens, or progestins, were designed to mimic progesterone (P4 ) for use in contraception and hormonal replacement therapy in women. Medroxyprogesterone acetate (MPA) and norethisterone (NET) are the most widely used injectable contraceptives in the developing world, while other progestins such as levonorgestrel (LNG), etonogestrel (ETG) and nestorone (NES) are used in or being developed for other forms of contraception. As concerns remain about the most appropriate choice of progestin and dosage, and the associated side-effects, the mechanisms and biological effects of progestins are frequently investigated in various in vitro mammalian cell line and tissue models. However, whether progestogens are differentially metabolised in different cell types in vivo or in vitro is unknown. For nine mammalian cell lines commonly used to investigate progestogen mechanisms of action, we developed and validated an ultra-high performance supercritical fluid chromatography-tandem mass spectrometry (UHPSFC-MS/MS) protocol for simultaneously quantifying the metabolism of the above-mentioned steroids. We show for the first time that, while 50–100% of P4 was metabolised within 24 h in all cell lines, the metabolism of the progestins is progestin- and cell line-specific. We also show that MPA and NET are significantly metabolised in human cervical tissue, but to a lesser extent than P4 . Taken together, our findings suggest that differential progestogen metabolism may play a role in cell-specific therapeutic and side-effects. Relative affinities for binding to steroid receptors as well as potencies, efficacies and biocharacters for transcriptional activity of progestins, relative to P4, are most frequently determined using some of the cell lines investigated. Our results, however, suggest that differential metabolism of progestins and P4 may confound these results. In particular, metabolism may under-estimate the receptor-mediated intrinsic in vitro binding and dose-response values and predicted endogenous physiological effects of P4 .